Vertical Sediment Drilling Technique in Fish-Pond Areas of Lake Limboto - Muhlis Ali; Raghel Yunginger; Septiana Kurniasari; Indriati Martha Patuti; Idawati Supu; Nurfitri Abd Gafur; Mursalin Mursalin; Mohamad Jahja; Andi Indra Wulan Sari Ramadani (MO.RI Publishing, 2026)
Lake Limboto in Gorontalo is an essential ecosystem for local communities, particularly fishermen, yet fish-pond activities have increased sedimentation and accelerated the lake's degradation. Effective conservation efforts require sediment-characterization analysis, including vertical sediment profiles in pond areas, which has been limited by the lack of appropriate drilling techniques. This study aims to evaluate a vertical sediment-sampling technique in fish-pond zones using a survey method and shallow drilling with an XY-1A spindle-type drilling machine at depths of 1–15 meters. The results indicate that drilling stability is strongly influenced by the structural integrity of the machine's support base, particularly due to water currents and waves in the lake. This drilling technique is recommended for sediment sampling in Lake Limboto, especially in pond areas, and contributes to the advancement of sediment-drilling methods in similar aquatic environments.